Cholelithiasis in liver cirhosis - Kadir AKSÖZ; Belkıs ÜNSAL; Günay ÖNDER; Nafi YAZICIOĞLU; M. KARADAĞ; Uğur GÖNENÇ; Ali ERGİN and Zakir AKYOL and Himmet KARACA and Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-